Studies on Heterosis for Yield and Yield Contributing Characters in Ridge Gourd (Luffa acutangula L.) - Wakale, D. G.; Jagtap, V. S.; Sogam, O. A. (International Journal of Bio-resource and Stress Management, 2018)
Half diallel analysis was carried out during kharif- 2016 at Instructional-Cum-Research Farm, Department of Horticulture, College of Agriculture, Latur, Vasantrao Naik Marathwada Krishi Vidyapeeth, Parbhani to study the heterosis per cent for yield and yield contributed characters. The 21 F1 hybrids along with their seven parent ware evaluated. Observation wererecorded on five randomly selected tagged plant from each treatment for yield and yield attributing character viz., length of vine, no. of nodes plant-1, length of fruit, diameter of fruit, no. of fruit vine-1, wt. of fruit, no. of fruit vine-1, wt. of fruit, wt. of fruit vine-1, fruit yield ha-1. The values of F1 averaged over replications were used for estimating heterosis. Manifestation of heterosis of higher order for number of fruit vine-1, length of fruit, weight of fruit, weight of fruit vine-1 and fruit yield ha-1. The maximum heterosis over better parent for fruit yield ha-1 was observed to be 38.58% and that over useful heterosis was found 84.42%. Three potential heterosis cross combinations viz. Arka Sujat×Krishna-51, Krishna-51×Kranti-30 and Krishna-51×Swati Green were identified as for promising for fruit yield per ha-1 The significant heterosis crosses involved high×high, low×high, low×low and high×low performance of parents. They have also exhibited higher additive variance. Hence, they may be exploited for development of hybrid in ridge gourd.